2017
DOI: 10.1111/cxo.12523
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of optical coherence tomographic parameters in subjects with a positive family history of glaucoma

Abstract: In individuals who have a history of POAG in their first-degree relatives, OCT parameters including retinal nerve fibre layer and ganglion cell complex are significantly lower than the subjects without a family history. Retinal nerve fibre layer and ganglion cell complex thinning were detected in normal-looking discs. The importance of these findings remains uncertain. Prospective, controlled clinical trials with longer follow up are necessary to understand, whether or not those changes are an early indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Comparable diagnostic capability of GC-IPL to that of RNFL thickness measurements has been reported for PPG. [ 16 17 ] Kim et al . reported that the inner directional angle of RNFL defects affected the diagnostic sensitivity of macular GC-IPL parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable diagnostic capability of GC-IPL to that of RNFL thickness measurements has been reported for PPG. [ 16 17 ] Kim et al . reported that the inner directional angle of RNFL defects affected the diagnostic sensitivity of macular GC-IPL parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Recently it has been found that significantly lower RNFL and GCC measurements were present in normal looking discs of individuals with a history of POAG in their first-degree relatives, compared to individuals without a similar history. [ 16 ] Lee and associates, found that inferotemporal thickness on GC-IPL had the best AUC in a study comprising wide field RNFL maps in eyes with PPG. [ 19 ] Inuzuka studied 77 eyes of PPG and reported that GC-IPL thicknesses in the inferior and inferotemporal sectors might serve as useful parameters to track the progression of glaucomatous changes in eyes with PPG.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have evaluated GCA for preperimetric glaucoma diagnosis have reported comparable diagnostic capability to that of RNFL thickness measurements. [ 27 28 ] Kim et al . [ 26 ] reported that the inner directional angle of RNFL defects affected the diagnostic sensitivity of macular ganglion cell-inner plexiform layer parameters in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Karti et al . [ 28 ] reported significantly lower RNFL and ganglion cell complex measurements in normal looking discs of individuals who had a history of POAG in their first-degree relatives, compared to individuals without a family history. Jung et al .,[ 29 ] in a structure-function relationship study, reported that preperimetric glaucoma patients with structural loss in the macula also had functional loss revealed by 10-2 short-wavelength automated perimetry, even though 24-2 visual fields were normal.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in nasal quadrant RNFL thickness between POAG suspect and controls (72.93±16.69 μm versus 77.08±9.28 μm, p=0.096). Karti et al, reported significantly lower RNFL and ganglion cell complex measurements in normal looking discs of individuals who had a history of POAG in their first-degree relatives, compared to individuals without a family history 32.…”
mentioning
confidence: 99%